Empowering Halal Food MSMEs through Koperasi Merah Putih: Pathways to Inclusive Economic Development in South Sulawesi - Nurfitriani Nurfitriani; Syaripuddin Syaripuddin (Journal of Innovative and Creativity, 2026)
This study explores the role of Islamic cooperatives in empowering halal micro, small, and medium enterprises (MSMEs) as a pathway to inclusive and sustainable economic development in South Sulawesi, Indonesia. It aims to assess how community-based models, particularly Koperasi Merah Putih, support halal MSMEs through Sharia-compliant financing, certification facilitation, and digital capacity building. Employing a qualitative case study methodology, the research was conducted in five districts with purposive sampling of cooperative members, MSME owners, and institutional stakeholders. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using thematic methods rooted in Islamic economic frameworks. The findings reveal that profit-sharing contracts such as mudharabah and musyarakah significantly enhance financial inclusion, while collective halal certification models reduce costs and procedural complexity. Digital transformation initiatives improve MSMEs’ market access and resilience, particularly when integrated with cooperative governance. Women entrepreneurs and rural actors benefit from enhanced opportunities, despite facing structural barriers. The study concludes that cooperative-based halal ecosystems “anchored in ethical finance and collective empowerment” offer a viable strategy for inclusive development and Islamic economic justice. It recommends further institutional support and policy innovation to replicate and scale the model across other regions.